1991
DOI: 10.2307/1591297
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Marek's Disease Virus DNA Transfection by a Sequence Containing an Alphaherpesvirus Origin of Replication and Flanking Transcriptional Regulatory Elements

Abstract: A co-transfection method was used to identify regions of the Marek's disease virus (MDV) genome that inhibit plaque formation when introduced along with total DNA from MDV-infected chicken embryo fibroblasts into secondary chicken embryo fibroblasts. Co-transfections involving MDV plasmids containing the BamHI-D or BamHI-H regions of the genome inhibited plaque formation more than 10-fold. The inhibitory region was localized to a 222-base-pair region that contains a sequence homologous to the consensus origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This could affect the binding of the UL9 Protein (originbinding protein) to this region thus reducing the replicative fitness of these attenuated strains. Compounding this is the fact that sequences encompassing the origin of replication (Ori) form a palindrome resembling microRNAs and this may be significant in light of research demonstrating plasmids containing the Ori sequences can reduce virus titers in transient assays [45]. Moreover, Niikura et al [46] have identified a cellular protein termed growth related translationally controlled tumor protein or (TCTP) that binds RLORF12 using a two hybrid approach.…”
Section: Discussionmentioning
confidence: 99%
“…This could affect the binding of the UL9 Protein (originbinding protein) to this region thus reducing the replicative fitness of these attenuated strains. Compounding this is the fact that sequences encompassing the origin of replication (Ori) form a palindrome resembling microRNAs and this may be significant in light of research demonstrating plasmids containing the Ori sequences can reduce virus titers in transient assays [45]. Moreover, Niikura et al [46] have identified a cellular protein termed growth related translationally controlled tumor protein or (TCTP) that binds RLORF12 using a two hybrid approach.…”
Section: Discussionmentioning
confidence: 99%
“…Because an ori sequence is found in the bidirectional promoter of pp38 and the 1.8 kb family RNA gene (BamHI-H), it is likely that in the late T9 cells MDV is unable to replicate. [56][57][58] Indeed, immunodiffusion performed with blood samples from chickens inoculated with late T9 cells did not reveal antibody against MDV (data not shown), confirming the fact that late T9 cells did not produce infectious viruses and were no longer capable of inducing Marek's disease.…”
Section: Discussionmentioning
confidence: 67%
“…Because an ori sequence is found in the bidirectional promoter of pp38 and the 1.8 kb family RNA gene (BamHI-H), it is likely that in the late T9 cells MDV is unable to replicate. [56][57][58] Indeed, immunodiffusion performed with blood samples from chickens inoculated with late T9 cells did not reveal antibody against MDV (data not shown), confirming the fact that late T9 cells did not produce infectious viruses and were no longer capable of inducing Marek's disease.…”
Section: Discussionmentioning
confidence: 78%